Blowout Morphometrics and Mass Balances - Baird, Thomas R.; Bristow, Charles S.; Luo, Wanyin; Du, Erji; Bryant, Robert G.; Mitchell, Thomas M.; Vermeesch, Pieter (Frontiers in Earth Science, 2021)
The Gonghe Basin on the Qinghai-Tibet Plateau has a cold, arid climate and has suffered severe land degradation. Climate change as well as anthropogenic activities including overgrazing have resulted in widespread blowout development and the formation of some of Earth's largest blowouts. The blowouts are part of an aeolian dominated landscape that passes from deflation zone to grass covered plain, and then through blowouts of increasing size and complexity to transverse barchanoid dunes that are migrating into the valley of the Yellow River. A combination of structure-from-motion (SfM) optical drone mapping, ground-penetrating radar (GPR) and soil pits are used to investigate blowout scour hollows and depositional lobes. Comparisons of the volumes of sediment removed from the scour hollows with the volumes of sediment deposited within adjacent lobes varies between sites. The lobe volume is invariably less than the volume of the scour hollow. This can, in part, be attributed to aeolian reworking of the lobe, distributing sand further downwind and uplifting of dust. However, much of the difference in volumes between the scour and lobe can be attributed to the measurement technique, particularly where GPR was employed to calculate lobe volumes. The wavelength of the GPR limits its ability to resolve thin layers of sand resulting in an underestimate of the deposited sand at the margins of a lobe where the sand thickness is equal to, or less than, the wavelength of the GPR. For thin sand layers, beneath the resolution of the GPR, soil pits suggest a closer match between the volume of sand eroded from the scour and the volume of the lobe, albeit with large measurement uncertainty. We put forth two hypotheses to explain the spatio-temporal evolution of the blowout dune field. The downwind increase in blowout dune size could either reflect a downwind propagation of aeolian instability; or it could result from an upwind propagation of the instability, which started at the highest points in the landscape and has subsequently migrated in a northwesterly direction, towards lower elevations. Recent optically stimulated luminescence dating appear to support the latter hypothesis.